Retaliation and Pardon as Expressed in Surah 5:45 With Reference to Matthew 5:38–42 - Dockrat, M. A. E. (Ashraf) (Journal for Semitics, 2017)
In Surah 5:45 retaliation and expiation are mentioned in close relation to one another. This leads to the question of the relation of the retribution clause to the forgiveness clause. Aspects such as the following come to the fore: • the comparative authority of the two statements; • the addressees of the retaliation and expiation clause; and • the contents and meaning of the two clauses. Qur’an 5:45 reminds one of Matthew 5:38-42. As in the case of the Qur’anic verse, Matthew 5:38-42 juxtaposes retaliation with non-retaliation, leading to questions such as the authority, addressees, and context of the respective statements. In this paper the surmised Jewish relationship of the Qur’anic and New Testament verses will be investigated. It will be argued that the Qur’anic focus on retaliation does not exclude pardoning and in the same vein the New Testament accent on expiation does not deny the validity of retaliation, accepting it as part of a common legal heritage. However the two traditions have contextualised retaliation and expiation in varying ways which can be expressed here in terms of the contents, the addressees, and authority.